2022
DOI: 10.1136/jnnp-2022-330150
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset epilepsy and risk of traumatic brain injury: a nationwide cohort study

Abstract: BackgroundA knowledge gap exists regarding the risk of traumatic brain injury (TBI) in patients with epilepsy.MethodsPatients with adult-onset epilepsy during 2005–2018 in Finland were studied using retrospective longitudinal national registry-linkage design. Patients with epilepsy (n=35 686; 51% men; mean age 56.6 years) were 1:1 matched to non-epileptic controls by age, sex, comorbidity burden and cohort entry year. The primary outcome was TBI leading to admission or death, secondary outcomes were TBI admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…More work is needed to determine if order of diagnosis of head injury vs seizure/epilepsy matters with regards to dementia risk; prior literature has shown a bidirectional association between head injury and epilepsy. 42 Indeed, our secondary analysis suggested that both PTE and head injury occurring after seizure/epilepsy were associated with increased dementia risk compared to head injury alone and seizure/epilepsy alone.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…More work is needed to determine if order of diagnosis of head injury vs seizure/epilepsy matters with regards to dementia risk; prior literature has shown a bidirectional association between head injury and epilepsy. 42 Indeed, our secondary analysis suggested that both PTE and head injury occurring after seizure/epilepsy were associated with increased dementia risk compared to head injury alone and seizure/epilepsy alone.…”
Section: Discussionmentioning
confidence: 78%
“…The pathophysiological mechanisms underlying the long-term sequelae of head injury and the development of PTE are complex, but a growing body of literature suggests that neurodegenerative mechanisms may contribute to both, providing biologic plausibility for the observed associations. More work is needed to determine if order of diagnosis of head injury vs seizure/epilepsy matters with regards to dementia risk; prior literature has shown a bidirectional association between head injury and epilepsy . Indeed, our secondary analysis suggested that both PTE and head injury occurring after seizure/epilepsy were associated with increased dementia risk compared to head injury alone and seizure/epilepsy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a possibility that prior seizures and diagnoses of epilepsy may have been missed in the exclusion process. Since patients with epilepsy have an increased risk of TBI compared with controls ( 41 ), this might have contributed to an overestimation of epilepsy in patients with TBI versus the control group. Despite these limitations, the use of extensive nationwide registers resulting in a large sample size representing the total population of hospital-admitted patients with TBI, the use of a matched control group and the competing risk analysis, accounting for the increased risk of death among patients with TBI, ensure valid and up-to-date estimates of the cumulative incidence of PTE.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying cause remains unclear; proposed explanations include the loss of consciousness during seizures, an atonic state, the frailty of the affected population, and antiepileptic drug side effects. TBIs in people with epilepsy are also more repetitive and more frequently fatal when compared to the population without epilepsy [19,20].…”
Section: Epidemiologymentioning
confidence: 99%